ANALYSIS OF ADULT PRODUCT ADS VIOLATIONS FACEBOOK DIMARKETPLACE REVIEW FROM BUSINESS ETHICS - Adinda Cahyaningrum; Revano Danendra (DUTA BANGSA UNIVERSITY INDONESIA, 2021)
Marketplace on social media is one of the special features for advertising/offering various categories of goods and services. The number of business actors making promissory notes on the Facebook marketplace has led to various violations of business ethics. As in the case that I raised this time, several adult product advertisements in which the form of advertisements contained pornographic images were clearly displayed, as well as the ad's showtime did not know the time and had no limits. Which is a norm regarding the iklas of adult products, many minors can access it anytime, anywhere on Facebook social media.